Ethanol Sensors Fabricated from PdO/WO3 Nanorods - Sathukarn Kabcum (Science Faculty of Chiang Mai University, 2019)
In this work, ethanol sensing films were prepared by spin-coating of PdO/WO3 nanorods pasted onto Al2O3 substrates interdigitated with Au electrodes and tested towards 50-2000 ppm C2H5OH at different operating temperatures ranging from 150–350°C. It was found that the C2H5OH responses of PdO-loaded WO3 sensors monotonically increased with increasing operating temperature to 350°C and increased greatly with increasing PdO-loading level up to 1.0 wt%. In particular, the optimal 1.0 wt% PdO-loaded sensor exhibited an ultra-high response of 1.52 ×104 to 2000 ppm C2H5OH at 350ºC with a short response time of ~3 s. In addition, PdO–loaded WO3 sensing films displayed high ethanol selectivity against CO, NO2, NH3 and H2S. Therefore, PdO-loaded WO3 nanorods sensors prepared by the precipitation and impregnation methods are promising for highly sensitive and selective for ethanol sensing.